Anne Molloy Correspondence - Molloy, Anne Stearns Baker, 1907-1999; Howells, Mrs. John Noyes Mead, 1907-1999; Jacob, Hilda McLeod; Thayer, Shirley, 1919-2001 (Digital Maine, 2015)
Entries include a typed biography and handwritten and typed letters.